The Role of Leading Teachers in Improving the Quality of Education in Elementary Schools - Kamaluddin, Roid; Hendrowati, Tri Yuni; Arman, Arman (Lembaga Riset Mutiara Akbar, 2025)
This study aims to determine the role of driving teachers to improve the quality of education in elementary schools in Sumberejo District, Tanggamus Regency. The sub-focus of this study includes how driving teachers move learning communities in schools and in their areas, how driving teachers accompany fellow teachers regarding learning development, how driving teachers improve student leadership in schools, how driving teachers open discussion spaces or collaboration with stakeholders to improve the quality of learning, how driving teachers as learning leaders who focus on the welfare of the educational ecosystem in schools, how to overcome obstacles or constraints in implementing improvements for driving teachers in improving the quality of education. Data were obtained through interviews, observations, and documentation. The results of the study indicate that the role of driving teachers in improving the quality of education faces various obstacles, such as lack of support from the principal, fellow teachers, and policy makers, as well as limited communication and coordination. This study recommends that to optimize their role, full support from various parties, increased coordination, and responsive policies are needed to optimize the role of driving teachers in improving the quality of education.